2019
DOI: 10.1186/s13059-019-1786-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rumen development in neonatal ruminants through microbial metagenomes and host transcriptomes

Abstract: Background In ruminants, early rumen development is vital for efficient fermentation that converts plant materials to human edible food such as milk and meat. Here, we investigate the extent and functional basis of host-microbial interactions regulating rumen development during the first 6 weeks of life. Results The use of microbial metagenomics, together with quantification of volatile fatty acids (VFAs) and qPCR, reveals the colonization of an active bacterial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 57 publications
12
94
0
Order By: Relevance
“…Among the four groups, the bacterial community colonized the rumen before day 7, which is similar to studies on dairy calves. For example, previous studies revealed that bacteria were detected in the rumen of dairy calves as early as birth and for the first week (1-7 days) of age [21,33,34], suggesting that rumen bacterial colonization occurs before the intake of solid food. The predominant bacterial phylum, Bacteroidetes, was found across all age groups, and the relative abundance of this phylum reached a maximum at 6 months of age, which is similar to the changes in the rumen of dairy cows from birth to 2 years of age [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among the four groups, the bacterial community colonized the rumen before day 7, which is similar to studies on dairy calves. For example, previous studies revealed that bacteria were detected in the rumen of dairy calves as early as birth and for the first week (1-7 days) of age [21,33,34], suggesting that rumen bacterial colonization occurs before the intake of solid food. The predominant bacterial phylum, Bacteroidetes, was found across all age groups, and the relative abundance of this phylum reached a maximum at 6 months of age, which is similar to the changes in the rumen of dairy cows from birth to 2 years of age [21].…”
Section: Discussionmentioning
confidence: 99%
“…Biogeographic patterns that are influenced by interactions with symbionts have also been noted in consortial gut symbioses. A recent study showed that the monogastric gut of a newborn ruminate requires interactions with microbial symbionts to differentiate into the characteristic chambered stomach with the rumen, reticulum, and oma- on November 3, 2020 by guest http://mbio.asm.org/ sum (43). In addition, symbiont colonization of germfree mice leads to changes in the epithelium of the gastrointestinal tract, such as the shortening of the intestine (44) and the generation of adaptive lymphoid tissues (45).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding newborn ruminants, gut function develops differently to other species [6,7]. When the rumen is not sufficiently developed and does not yet have ruminant function, digestion patterns of neonate kids are mostly dependent on the small and large intestines [8], and are more similar to those of monogastric animals. During the development of the rumen from the nonfunctional phase to the ruminant phase, the major digestive compartment moves from the intestine to the rumen since the metabolites shift from glucose to volatile fatty acids [7].…”
Section: Introductionmentioning
confidence: 99%